Adaptación de lente de contacto blandos tóricos en paciente de masculino 38 años con miopía magna. - Rodríguez Rodríguez, Nelson Jonathan (2023)
High myopia is a refractive problem that affects the quality of life of those who suffer from it. Its main characteristics are blurred distance vision and low visual acuity. In the present clinical case we have a 38-year-old male patient in whom high myopia and astigmatism were detected. The main objective is to adapt soft toric lenses, the patient presented symptoms such as blurred vision, headache, and photophobia. Eye examinations and diagnostics were performed. Subjective refraction and keratometry. Magna myopia with compound myopic astigmatism was diagnosed. Toric soft contact lenses were fitted, monthly check-ups were performed to evaluate visual status, and an annual ophthalmological check-up was performed to verify any anomaly. It is concluded that the adaptation was successful and the quality of life of the patient under study was significantly improved.